Transcriptome and IgH Repertoire Analyses Show That CD11chi B Cells Are a Distinct Population With Similarity to B Cells Arising in Autoimmunity and Infection - Maul, Robert W.; Catalina, Michelle D.; Kumar, Varsha; Bachali, Prathyusha; Grammer, Amrie C.; Wang, Shu; Yang, William; Hasni, Sarfaraz; Ettinger, Rachel; Lipsky, Peter E.; Gearhart, Patricia J. (Frontiers in Immunology, 2021)
A distinct B cell population marked by elevated CD11c expression is found in patients with systemic lupus erythematosus (SLE). Cells with a similar phenotype have been described during chronic infection, but variable gating strategies and nomenclature have led to uncertainty of their relationship to each other. We isolated CD11chi cells from peripheral blood and characterized them using transcriptome and IgH repertoire analyses. Gene expression data revealed the CD11chi IgD+ and IgD− subsets were highly similar to each other, but distinct from naive, memory, and plasma cell subsets. Although CD11chi B cells were enriched in some germinal center (GC) transcripts and expressed numerous negative regulators of B cell receptor (BCR) activation, they were distinct from GC B cells. Gene expression patterns from SLE CD11chi B cells were shared with other human diseases, but not with mouse age-associated B cells. IgH V-gene sequencing analysis showed IgD+ and IgD− CD11chi B cells had somatic hypermutation and were clonally related to each other and to conventional memory and plasma cells. However, the IgH repertoires expressed by the different subsets suggested that defects in negative selection during GC transit could contribute to autoimmunity. The results portray a pervasive B cell population that accumulates during autoimmunity and chronic infection and is refractory to BCR signaling.